Vesicle-to-micelle transition in aqueous mixtures of cationic lipids with Pluronic F127 - Feitosa, Eloi [UNESP] (2023)
Aqueous solutions of vesicle-forming lipids mixed with micelle-forming copolymers may result in stabilized and biocompatible aggregates. Differential scanning calorimetry (DSC) and dynamic light scattering (DLS) techniques were used here to investigate the effects of the nonionic triblock copolymer Pluronic F127 (F127) on the thermal behavior, structural changes, and hydrodynamic size of cationic vesicles from dioctadecyldimethylammonium chloride (DODAC), dioctadecyldimethylammonium bromide (DODAB), and didodecyldimethylammonium bromide (DDAB) in aqueous dispersion. The DSC thermograms indicate that upon the addition of up to 5.0 mM F127, a vesicle-to-micelle transition occurs in three stages. First, there is a predominance of lipid-F127 mixed vesicles, followed by the co-existence of mixed vesicles and micelles, and finally, the system is dominated by mixed micelles. DLS results reveal that with the addition of F127 to the lipid dispersions, the size of the assembled structures tends to decrease, also indicating structural changes of vesicles to micelles. These results indicate that the borders between these stages depend on the lipid chain length and counterion type.